Pengendalian Hayati Penyakit Layu Bakteri Tembakau: 2. Percobaan di Rumah Kaca - Triwidodo Arwiyanto; I. Hartana (Jurnal Perlindungan Tanaman Indonesia, 1999)
Tobacco bacterial wilt caused by Ralstonia solanacearum has been controlled biologically in the greenhouse by the use of rhizosphere microorganisms, i.e. fluorescent pseudomonads and Bacillus spp. Root dipping for 30 minutes in the antagonist suspension (108 cfu/ml) suppressed bacterial wilt development. The best results were obtained with fluorescent pseudomonads Pf-20 and Bacillus sp. ba-118 isolates but the repression was annulled with the use of its combination. Disease severity were higher when the plants were treated with the combination between fluorescent pseudomonads. Treatment combinations between Pf-28, Pf-31, Pf-33, and Ba-118 could reduce the disease index.